Influential leadership a leader's guide to getting things done - Gautrey, Colin (Kopan Page Limited, 2014)
This book is about action, results and leadership. Using a simple new framework, it will show you how to make the sort of progress in your work which your organization wants and needs. At the same time, this progress will give you the space to become a real leader. A leader who is strong, inspirational, and able to drive the results your company needs while keeping your people on board. One of the best ways to create the time you need to get results and get ahead is to become highly influential - that way, you don't have to do it all yourself. Influential Leadership will show you practical ways to become more influential and create the time you need to be the most effective leader you can be